2021
DOI: 10.1016/j.hroo.2021.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Early experiences with three types of balloon-based ablation catheters in patients with paroxysmal atrial fibrillation

Abstract: BACKGROUND Although balloon-based ablation catheters are expected to improve the feasibility and quality of pulmonary vein isolation (PVI) in patients with atrial fibrillation (AF), they must be introduced to physicians in the proper setting to ensure their correct usage.OBJECTIVE To identify the optimal clinical settings for learning the techniques for 3 balloon-based ablation catheters (Cryoballoon, Hotballoon, and Laserballoon).METHODS We introduced 3 balloon catheters in 50 consecutive patients with paroxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…Previous studies have reported that acute PV isolation using an LB1 alone with the point-by-point technique reached a sufficiently high success rate even with a certain long procedure time. 9,14 In this study, the PV isolation rate using an LB1 alone with the novel dragging technique reached a comparably high rate with a shorter procedure time than the conventional point-by-point technique. In RF ablation, a certain number of PVs have been observed to reconnect after ablation due to a noncontiguity between the point-by-point lesions along the ablation line.…”
Section: Efficacy Of the Dragging Methodsmentioning
confidence: 62%
See 1 more Smart Citation
“…Previous studies have reported that acute PV isolation using an LB1 alone with the point-by-point technique reached a sufficiently high success rate even with a certain long procedure time. 9,14 In this study, the PV isolation rate using an LB1 alone with the novel dragging technique reached a comparably high rate with a shorter procedure time than the conventional point-by-point technique. In RF ablation, a certain number of PVs have been observed to reconnect after ablation due to a noncontiguity between the point-by-point lesions along the ablation line.…”
Section: Efficacy Of the Dragging Methodsmentioning
confidence: 62%
“…To create continuity and transmural ablation lesions using LB1, it is recommended to overlap the laser irradiation applications by 30–50% 8 . However, this conventional method leads to an increase in the frequency of laser irradiations and the duration of the procedure 9 . The third‐generation LB (LB3) with an automated dragging system has been reported to shorten the duration of the procedure 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…Because the cryoballoon is non-compliant, it is difficult to occlude a PV that has been deformed into a teardrop or severe oval shape due to vertebral body compression or to dilate the balloon in a LA that is considerably less than the balloon diameter; therefore, such patients are less indicated for cryoballoon PVI. 4 Eligible patients for cryoballoon ablation were selected based on preprocedural computed tomography (CT) images, and patients who had a severely thin LA or deformed PV were excluded. PVI was performed in all cases using a cryoballoon (cryoballoon group) or RF catheter (CFRF group).…”
Section: Study Patientsmentioning
confidence: 99%
“…Cryoballoon Ablation The cryoballoon ablation procedure was performed as previously described. 4 Briefly, after voltage mapping of the LA and PV, a 15-Fr steerable sheath (FlexCath Advance, Medtronic Inc., MN, USA) was placed. A 28-mm second-or fourth-generation cryoballoon (ArcticFront Advance, or ArcticFront Advance Pro, Medtronic Inc.) was inflated at the orifice of each PV and anchored using a 20-mm circular mapping wire catheter with 10-pole electrodes (Achieve, Medtronic Inc.).…”
Section: Ablationmentioning
confidence: 99%
See 1 more Smart Citation